2019
DOI: 10.1039/c9sc00800d
|View full text |Cite
|
Sign up to set email alerts
|

Designing stable, hierarchical peptide fibers from block co-polypeptide sequences

Abstract: Here we report the pH induced self-assembly of equilibrium zwitterionically charged block co-polypeptide nanotubes into hierarchical nanotube fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Nanotube formation was also observed in a series of amphiphilic block co-polypeptides Ac-[ALV] x - b -[KGE] y -NH 2 ( x + y = 7) (Van Rijt et al ., 2019). TEM analysis indicated that peptide Ac-[ALV] 3 - b -[KGE] 4 -NH 2 self-assembled to form high aspect-ratio nanotubes of ~90 Å in diameter that were stable over a wide pH range (pH = 2–12) and at temperatures up to 80 °C.…”
Section: Cross-β Nanotubesmentioning
confidence: 99%
“…Nanotube formation was also observed in a series of amphiphilic block co-polypeptides Ac-[ALV] x - b -[KGE] y -NH 2 ( x + y = 7) (Van Rijt et al ., 2019). TEM analysis indicated that peptide Ac-[ALV] 3 - b -[KGE] 4 -NH 2 self-assembled to form high aspect-ratio nanotubes of ~90 Å in diameter that were stable over a wide pH range (pH = 2–12) and at temperatures up to 80 °C.…”
Section: Cross-β Nanotubesmentioning
confidence: 99%
“…Thermodynamically controlled processes tend to result in predictable and well-defined structures. However, their application is limited by their sensitivity to changes in the environment, which can significantly alter the formed structures 7,8 . Kinetically controlled processes tend to result in stable structures, but the final structures can be highly sensitive to the assembly method 5,7,9 .…”
mentioning
confidence: 99%
“…However, their application is limited by their sensitivity to changes in the environment, which can significantly alter the formed structures 7,8 . Kinetically controlled processes tend to result in stable structures, but the final structures can be highly sensitive to the assembly method 5,7,9 . While the final structural dependence on assembly methodology offers the flexibility to form multiple hierarchical structures from a single BCP, it necessitates strict control of the synthetic conditions 3,7,10 .…”
mentioning
confidence: 99%
“…Peptide secondary structure has been shown to influence the self-assembly of peptide-containing conjugates; [27,[32][33][34][35] this is further confounded by the ability of steric crowding to induce secondary structure in peptides. [28,36] Therefore, to focus on the effect of peptide hydrophilicity on self-assembly we used two classes of unstructured peptides-PAS [37] and XTEN [38][39][40] -and from these, selected a total of four sequences that vary in length and charge density (Figure 1b, Figures S11-S14).…”
Section: Scope Of Design Space and Synthesis Of Ppasmentioning
confidence: 99%